Neurologic and psychiatric features of impending neurodegeneration in iRBD - Daniel A. Barone; Harini Sarva; Natalie Hellmers; Fei Wang; Zhenxing Xu; Ana C. Krieger; Claire Henchcliffe (Clinical Parkinsonism & Related Disorders, 2023)
Introduction: Idiopathic rapid eye movement (REM) sleep behavior disorder (iRBD) is linked to Parkinson’s disease and other alpha-synucleinopathies, but various subsets of iRBD may not carry equal risk (i.e., those with depression are at higher risk than those without). Here, we prospectively focus on neurologic and psychiatric aspects of subjects with iRBD, in an attempt to determine what factors are prominent in those who undergo phenoconversion as opposed to those who do not. Methods: We analyzed data from the “REM Sleep Behavior Disorder Associations with Parkinson’s Disease Study (RAPiDS)” cohort both at baseline and then at follow-up evaluations (1 to 3 years later) utilizing several neurologic batteries, including the Movement Disorder Society’s Unified Parkinson’s Disease Rating Scale (MDS-UPDRS), the Montreal Cognitive Assessment (MoCA), the Questionnaire for Impulsive-Compulsive Disorders in Parkinson’s Disease (QUIP), the 10-M Walk Test (10MWT), and the Epworth Sleepiness Scale. Determination of phenoconversion was ascertained from physical examination and medical chart review from the initial evaluation onward. Results: Of those who completed both evaluations, there were 33 subjects with iRBD, with an average age of 63.1 ± 12.8 years, with 9 women and 24 men. Of these, 8 (24%) iRBD subjects developed neurodegenerative illness, and demonstrated multiple areas of neurologic and psychiatric signs and symptoms, such as speech and movement problems as well as anxiety and depression. Conclusions: Our data adds to the literature regarding risk of phenoconversion in those with iRBD. Further study will be needed, but it is clear that not all subjects with iRBD present the same risk for neurodegeneration.